Thalassaemia types and their incidence in Sardinia. - Cao, A (1978)
The frequency of thalassaemia syndromes in Sardinia was examined by a population survey. The data indicate that about 12.6% of the Sardinian subjects are carriers of beta-thalassaemia, while 6.9% of the population carries an alpha-thalassaemia gene, with a slight difference between the various provinces. These are among the highest frequencies of thalassaemia genes found in a Caucasian population today. A survey of hospital inpatients and outpatients showed a newborn incidence of homozygous beta-thalassaemia of 1 in 300. The reasons for the difference between the expected and observed incidence figures are discussed. Moreover, 3 subjects with deltabeta0-thalassaemia trait, 6 carriers of heterocellular persistence of fetal haemoglobin (HPFH), 1 sickle cell trait, and 3 subjects with Hb J Sardegna were found. Genetic heterogeneity of beta-thalassaemia syndromes in this population may generally result from interaction of alpha- and beta-thalassaemia genes.